Alethopteris and Neuralethopteris from the lower Westphalian (Middle Pennsylvanian) of Nova Scotia and New Brunswick, Maritime Provinces, Canada - Álvarez-Vázquez, Carmen (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2020)
A systematic revision of Alethopteris and Neuralethopteris from upper Namurian and lower Westphalian (Middle Pennsylvanian) strata of Nova Scotia and New Brunswick, eastern Canada, has demonstrated the presence of eight species: Alethopteris bertrandii, Alethopteris decurrens, Alethopteris cf. havlenae, Alethopteris urophylla, Alethopteris cf. valida, Neuralethopteris pocahontas, Neuralethopteris schlehanii and Neuralethopteris smithsii. Restudy of the Canadian material has led to new illustrations, observations and refined descriptions of these species. Detailed synonymies focus on records from Canada and the United States. As with other groups reviewed in earlier articles in this series, it is clear that insufficient attention has been paid to material reposited in Canadian institutions in the European literature. The present study emphasizes the similarity of the North American flora with that of western Europe, especially through the synonymies.